Assessing ground covers in a newly planted apple orchard - Hartley, M.J.; Rahman, A.; Harrington, K.C.; James, T.K. (New Zealand Plant Protection, 2000)
Three low growing groundcover species dichondra (Dichondra micrantha) hydrocotyle (Hydrocotyle heteromeria) and a creeping red fescue (Festuca rubra)/white clover (Trifolium repens) mixture were compared to bark mulch and herbicide in a newly planted apple orchard for their ability to suppress weeds Dichondra with the aid of an initial herbicide treatment established a dense ground cover and provided good weed suppression Hydrocotyle failed to establish under the dry Hawkes Bay conditions Creeping red fescue gave moderate weed suppression Bark required spot treatment with herbicide for complete weed control All ground covers reduced tree growth and fruit yield in the first year compared to herbicide and bark mulch